2021
DOI: 10.3390/ph14040318
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Adipose-Derived Mesenchymal Stem Cells Combined with Shockwave Therapy Synergistically Ameliorates the Osteoarthritic Pathological Factors in Knee Joint

Abstract: Adipose-derived mesenchymal stem cells (ADSCs) and shockwave (SW) therapy have been shown to exert a chondroprotective effect for osteoarthritis (OA). The results of this study demonstrated that autologous ADSCs had dose-dependent and synergistic effects with SW therapy (0.25 mJ/mm2 with 800 impulses) in OA rat knee joint. Autologous, high-dose 2 × 106 ADSCs (ADSC2 group) combined with SW therapy significantly increased the bone volume, trabecular thickness, and trabecular number among in the treatment groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 47 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…Seventeen studies evaluated the effects by imaging analysis: nine studies (52.9%) reported significant differences in favour of adipose-derived products, while eight studies observed no differences. In particular, micro-computed tomography (micro-CT) evaluation was performed in six studies, with positive effects in five studies in terms of prevention of cartilage and subchondral bone degeneration and improvement of bone thickness and volume [23][24][25][26][27]. Radiographic evaluation was performed in 6 studies with only one study showing a statistically significant difference in favour of adipose-derived products [28].…”
Section: Imaging Analysismentioning
confidence: 99%
“…Seventeen studies evaluated the effects by imaging analysis: nine studies (52.9%) reported significant differences in favour of adipose-derived products, while eight studies observed no differences. In particular, micro-computed tomography (micro-CT) evaluation was performed in six studies, with positive effects in five studies in terms of prevention of cartilage and subchondral bone degeneration and improvement of bone thickness and volume [23][24][25][26][27]. Radiographic evaluation was performed in 6 studies with only one study showing a statistically significant difference in favour of adipose-derived products [28].…”
Section: Imaging Analysismentioning
confidence: 99%
“…The SW group animals received SW treatment using an SW device DUOLITH SD1 (STORZ MEDICAL AG, Tägerwilen, Switzerland). A shockwave was applied to the subchondral bone of the medial tibial condyle of the left knee at 0.5 cm below the joint line and 0.5 cm from the medial skin surface [29]. Each knee received 800 pulses of SW at 0.25 mJ/mm 2 energy flux density of 4 Hz.…”
Section: Shockwave Applicationmentioning
confidence: 99%
“…Preparation of rat adipose-derived MSCs (ADSCs) was performed as described in our previous study [29,30]. Briefly, rat ADSCs were isolated from subcutaneous adipose tissues of SD rats at 8 weeks of age.…”
Section: Isolation Of Rat Adipose-derived Mscsmentioning
confidence: 99%
See 2 more Smart Citations